Elections and Voters in Britain - Denver, David. author. aut Link
XI, 273 p.
Keywords: • How do voters in Britain decide which party to vote for in elections? • Why do smaller parties get more support than they used to? • How do the mass media influence political opinions? The authors examine these and other questions in the third edition of this popular text. They trace the evolution of the British electorate over the post-war period, and focus in particular on recent elections – from Labour's victories in the 2000s through to the hung parliament of 2010. As well as examining and explaining theories of party choice – including the view that voters' evaluations of government performance and party leaders are now the key determinants of election outcomes – the authors also devote separate chapters to turnout trends and patterns, electoral systems and the geography of party support. Campaigning, opinion polls and the mass media are also considered. Fully revised, the text incorporates the latest research on elections and voting behaviour, and includesanalysis of recent trends and developments – including how 'new media' are affecting election campaigning.